2012
DOI: 10.1111/j.1474-9726.2011.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong rapamycin administration ameliorates age‐dependent cognitive deficits by reducing IL‐1β and enhancing NMDA signaling

Abstract: Summary Understanding the factors that contribute to age-related cognitive decline is imperative, particularly as age is the major risk factor for several neurodegenerative disorders. Levels of several cytokines increase in the brain during aging, including IL-1β, whose levels positively correlate with cognitive deficits. Previous reports show that reducing the activity of the mammalian target of rapamycin (mTOR) extends lifespan in yeast, nematodes, Drosophila, and mice. It remains to be established, however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
144
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(155 citation statements)
references
References 46 publications
(84 reference statements)
8
144
1
1
Order By: Relevance
“…Addressing this question requires determining whether rapamycin delays a broad range of age-dependent functional and structural alterations in a number of different cell types, tissues, and organ systems. While some recent reports suggest that rapamycin may indeed prevent aging phenotypes in addition to age-related mortality and cancer (8,16,17), these reports are highly limited in scope, examining only a paucity of aging phenotypes and not accounting for potential aging-independent drug effects.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing this question requires determining whether rapamycin delays a broad range of age-dependent functional and structural alterations in a number of different cell types, tissues, and organ systems. While some recent reports suggest that rapamycin may indeed prevent aging phenotypes in addition to age-related mortality and cancer (8,16,17), these reports are highly limited in scope, examining only a paucity of aging phenotypes and not accounting for potential aging-independent drug effects.…”
Section: Introductionmentioning
confidence: 99%
“…If such an effect can be confirmed in a future larger scale trial, one possible explanation could be the anti-inflammatory effects of rapamycin reducing pain associated with arthritis. Rapamycin is also known to improve cognitive function in middle-aged mice (Halloran et al 2012;Majumder et al 2012), and it is possible that rapamycin could alter cognitive function in dogs in a way that induces these behavioral changes. It will be of particular interest to determine whether similar effects are observed in future longer term studies and to directly assess cognitive function and inflammatory state in dogs receiving rapamycin.…”
Section: Possible Effects Of Rapamycin On Behaviormentioning
confidence: 99%
“…Treatment with rapamycin increases lifespan in evolutionarily divergent organisms including yeast, nematodes, fruit flies, and mice (Johnson et al 2013;Johnson et al 2015). In addition to increasing lifespan, treatment with rapamycin has also been shown to improve a variety of age-associated conditions in mice, including reducing cancer incidence (Anisimov et al 2011), improving cognitive function (Halloran et al 2012;Majumder et al 2012), reversing cardiac (Dai et al 2014;Flynn et al 2013;Neff et al 2013) and immune (Chen et al 2009) declines, restoring stem cell function (Chen et al 2009;Yilmaz et al 2012), and improving muscle function (Bitto et al 2016;Fischer et al 2015) in aged animals. Of particular note, initiating treatment with rapamycin late in mid-life appears to increase longevity to an extent comparable to treatment beginning early in life (Harrison et al 2009), and one recent study reported increases in life expectancy from 20 to 60% following single transient treatments with rapamycin from 20 to 23 months of life in mice (Bitto et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic rapamycin treatment, however, did not ameliorate AD-like deficits when administered in the late stages of AD-like disease in the 3xTg-AD mouse model. 34 Whether rapamycin would improve cognitive outcomes and ameliorate AD-like histopathological deficits in hAPP(J20) mice modeling AD when administered after establishment of robust AD-like memory impairments (equivalent to the time at diagnosis of possible AD), however, was not known. To answer this question, in the present study we used behavioral and biochemical tools and in vivo optical brain imaging in conjunction, for the first time, with multimodal magnetic resonance imaging (MRI) techniques in vivo to study the effects of rapamycin treatment on functional outcomes in a mouse model of AD.…”
Section: Introductionmentioning
confidence: 99%